2019
DOI: 10.3389/fneur.2018.01178
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Conversion From Amnestic Mild Cognitive Impairment to Alzheimer's Disease Based on the Brain Structural Connectome

Abstract: Background: Early prediction of disease progression in patients with amnestic mild cognitive impairment (aMCI) is important for early diagnosis and intervention of Alzheimer's disease (AD). Previous brain network studies have suggested topological disruptions of the brain connectome in aMCI patients. However, whether brain connectome markers at baseline can predict longitudinal conversion from aMCI to AD remains largely unknown.Methods: In this study, 52 patients with aMCI and 26 demographically matched health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 97 publications
2
23
0
Order By: Relevance
“…Our results exhibited that the functional networks of the SCD and aMCI patients also showed a small-world topology, which accords with previous studies ( Sun et al, 2014 , 2018 ). Compared with the HC, the aMCI showed significantly lower small-worldness, lower normalized clustering coefficient, and higher characteristic path length.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results exhibited that the functional networks of the SCD and aMCI patients also showed a small-world topology, which accords with previous studies ( Sun et al, 2014 , 2018 ). Compared with the HC, the aMCI showed significantly lower small-worldness, lower normalized clustering coefficient, and higher characteristic path length.…”
Section: Discussionsupporting
confidence: 93%
“…The altered σ, γ, and L p in the SCD and aMCI groups indicated the disturbed balance between local specialization and global integration ( Sun et al, 2014 ). Moreover, the aMCI group showed a significant decline in global efficiency compared with the HC, which was consistent with previous studies, also proving the potential mechanisms of disconnection in the AD spectrum ( Sun et al, 2018 ). More severe disruptions of network metrics were found in the aMCI patients relative to the SCD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent developments in non-invasive neuroimaging techniques, including functional and structural imaging, have given rise to a variety of commonly used neuroimaging biomarkers for AD. Among the multiple neuroimaging modalities, structural magnetic resonance imaging (sMRI) has attracted significant interest due to its ready availability for mildly symptomatic patients and its high spatial resolution ( Cuingnet et al, 2011 ; Salvatore et al, 2015 ; Wei et al, 2016 ; Long et al, 2017 ; Gupta et al, 2019b , c ; Sun et al, 2019 ). sMRI can also reveal abnormalities in a wide range of brain areas, including gray matter (GM) atrophy in the medial temporal lobe and hippocampal/entorhinal cortex, which are identified as valuable AD-specific biomarkers for the discrimination or classification of AD patients ( Cuingnet et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other neurologic diseases, it has already been shown that network features are predictive of outcomes. For subjects with mild cognitive impairment, network features were predictive of volumetric atrophy in 6 months and conversion to Alzheimer's Disease (Nir et al, 2015;Sun et al, 2019). Furthermore, progressive deterioration of the rich club organization dynamically reflects the progression of Alzheimer's Disease (Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 96%